2021
DOI: 10.1002/anie.202015362
|View full text |Cite|
|
Sign up to set email alerts
|

Sterilizing Immunity against SARS‐CoV‐2 Infection in Mice by a Single‐Shot and Lipid Amphiphile Imidazoquinoline TLR7/8 Agonist‐Adjuvanted Recombinant Spike Protein Vaccine**

Abstract: The search for vaccines that protect from severe morbidity and mortality because of infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the virus that causes coronavirus disease 2019 (COVID‐19) is a race against the clock and the virus. Here we describe an amphiphilic imidazoquinoline (IMDQ‐PEG‐CHOL) TLR7/8 adjuvant, consisting of an imidazoquinoline conjugated to the chain end of a cholesterol‐poly(ethylene glycol) macromolecular amphiphile. It is water‐soluble and exhibits massive tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…Passive transfer studies performed in NHPs suggest only low NAb titers are necessary for protection against homologous challenge ( 17 ). As the amount of serum transferred was small (150 μl/mouse), it is likely that with such high NAb titers, the number of vaccinations required for instilling sterilizing immunity can be reduced to two or even one with NE/IVT, as we have reported for IM SARS-CoV-2 vaccination in mice with a TLR7/8 agonist as adjuvant which induced significantly lower NAb titers ( 59 ). The ability of NE/IVT to improve cross-variant protection induced with just the S1 subunit, particularly towards a variant with the N501Y mutation shared by several of the highly transmissible variants of concern, supports its potential for improving the breadth of protection of current vaccine candidates.…”
Section: Discussionmentioning
confidence: 97%
“…Passive transfer studies performed in NHPs suggest only low NAb titers are necessary for protection against homologous challenge ( 17 ). As the amount of serum transferred was small (150 μl/mouse), it is likely that with such high NAb titers, the number of vaccinations required for instilling sterilizing immunity can be reduced to two or even one with NE/IVT, as we have reported for IM SARS-CoV-2 vaccination in mice with a TLR7/8 agonist as adjuvant which induced significantly lower NAb titers ( 59 ). The ability of NE/IVT to improve cross-variant protection induced with just the S1 subunit, particularly towards a variant with the N501Y mutation shared by several of the highly transmissible variants of concern, supports its potential for improving the breadth of protection of current vaccine candidates.…”
Section: Discussionmentioning
confidence: 97%
“…Of these, TLR3, TLR7, TLR8 and TLR9 mount antiviral immune responses: TLR3 recognizes double-stranded RNA viruses, TLR9 recognizes unmethylated CpG in viral DNA, and, relevant to coronaviruses, TLR7 and TLR8 bind G/U-rich single-stranded viral RNA. TLR7 and TLR8 reside in the endosomes and were shown to induce proinflammatory cytokines in response to SARS-CoV and SARS-CoV-2 RNA 146 , 147 . TLR7 and TLR8 are both expressed in lung tissue.…”
Section: Sars-cov-2 Entry Processmentioning
confidence: 99%
“…Output data from molecular dynamic simulations can be used to evaluate vaccine stability by simulation in vivo , wherein a study, the evaluation of TLR7/8 stimulation as in vivo , showed that injection of recombinant spike protein candidate vaccine in a mouse model induced the production of IgG2a and IgG1. (Jangra et al 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Although COVID-19 disease is still a relatively new disease and requires more clinical findings, studies have shown the importance of TLR7/8 stimulation in COVID-19 vaccines. In one study, Imidazoquinolines was used as an adjuvant in a SARS-CoV-2 recombinant spike protein vaccine to enhance TLR7/8 stimulation, and the results showed that the vaccine led to product the robust IgG2a and IgG1 antibody titers in a mouse model and neutralized viral infection in both in vitro and in vivo (Jangra et al 2021 ). Responses of Th1 and CD8 + T cells have been shown also against HIV-1 Gag protein as RNA viral infection by TLR7/8 agonist (Wille-Reece et al 2005a , 2005b ).…”
Section: Discussionmentioning
confidence: 99%